Research on hierarchical and sub‐area network control technology of LEO giant constellation - Ci He; Yasheng Zhang; Yuejun Yu; Cong Li (IET Communications)
Abstract The low‐earth‐orbit (LEO) telecommunication constellation network is foreseen as a merging interconnection method for future sixth‐generation (6G) systems. However, how to implement constellation system composition, consider network design constraints and envision application scenarios in a low‐orbit giant constellation system, is still an open problem. In this paper, by exploring the constellation characteristics in the future LEO systems, the design of hierarchical and sub‐area network control architecture for giant constellation is first suggested. After that, a detailed research on the partition mechanism of control domain for the giant LEO constellation systems is implemented. To make the architecture design and partition mechanism feasible, the hierarchical and domain controlling flow is also discussed. Finally, a performance verification method is present with elaborate numerical results and evaluations. The results verified the correctness and effectiveness of the proposed network control architecture and partition mechanism.